Respuesta :
11x + 4y = 18
3x + 4y = 2.....multiply by -1
----------------
11x + 4y = 18
-3x - 4y = -2 (result of multiplying by -1)
---------------add
8x = 16
x = 16/8
x = 2
3x + 4y = 2
3(2) + 4y = 2
6 + 4y = 2
4y = 2 - 6
4y = -4
y = -4/4
y = -1
solution is : (2,-1)
3x + 4y = 2.....multiply by -1
----------------
11x + 4y = 18
-3x - 4y = -2 (result of multiplying by -1)
---------------add
8x = 16
x = 16/8
x = 2
3x + 4y = 2
3(2) + 4y = 2
6 + 4y = 2
4y = 2 - 6
4y = -4
y = -4/4
y = -1
solution is : (2,-1)
11 x + 4 y = 18
3 x + 4 y = 2
11 x + 4 y = 18
- 3 x - 4 y = - 2
8 x = 16
x = 2
11 x + 4 y = 18
22 + 4 y = 18
4 y = 18 - 22
4 y = - 4
y = - 1
S ( - 1 ; 2)
3 x + 4 y = 2
11 x + 4 y = 18
- 3 x - 4 y = - 2
8 x = 16
x = 2
11 x + 4 y = 18
22 + 4 y = 18
4 y = 18 - 22
4 y = - 4
y = - 1
S ( - 1 ; 2)